KNOWLEDGE AND PRACTICES REGARDING FAMILY PLANNING IN A GROUP OF MEN IN ERBIL CITY - Dhiab, Amer Ahmed; Al-Tawil, Namir Ghanim (Journal of Sulaimani Medical College, 2017)
Background Men plays an integral role in the process of family planning (FP), but in spite of that the studies are scarce in Kurdistan region. Objectives To find out: the proportion of knowledge regarding FP in a group of men; the rate of utilization of FP methods; and the association of rate of utilization of FP methods with age, level of education, and occupation. Methods A cross-sectional study was conducted at Rizgary teaching hospital in Erbil city for the period from January 2, 2012 and ends in December 31, 2012. Convenience method of sampling was used to collect 500 married men attending Rizgary teaching hospital consultation clinics. An interview was done, using a questionnaire designed by the researchers. Results Majority of men (60.8%) has heard of the term ‘family planning’ and almost all (95.5%) had unacceptable answers regarding definition of FP. Nearly all husbands (96.8%) were aware of the common types of FP methods. The prevalence of utilization of F.P. methods was 71.2 %, more than one third of users (37.1%) used withdrawal, 32% used condom, 16.9% used Intrauterine Contraceptive Device (IUCD) and 11.2% used oral pills. There was significant association between the high rate of utilization of FP methods with age (≥ 40 years), and high rank occupations of men. Conclusion The majority of the sample had an acceptable knowledge about FP methods except for the definition of FP term. The study revealed high rates of utilization of FP methods. Older ages, and high rank occupations were associated with high rate of utilization of FP methods.
Keywords: Family planning; Knowledge; Practice; Prevalence